Burnout in Medical Student: Literature Review - Rawis, Joulanda A. M.; Lengkong, Andriessanto C.; Mahama, Inggrid C.; Lampah, Christopher; Posangi, Iddo (Syntax Literate, 2024)
Burnout is a condition of emotional exhaustion, depersonalization, and reduced work performance caused by chronic stress. Burnout can occur in various people, including medical students. The purpose of this study was to review the literature on burnout in medical students. This study used a literature research method. Research data were collected using literature search techniques. Research data were obtained from various sources, namely journal articles, books, and research reports. The research data were analyzed using qualitative analysis techniques. The results showed that burnout in medical students is a serious problem. Burnout can occur in medical students at various levels of education, ranging from early semester students to final semester students. Factors that can cause burnout in medical students include high academic loads, demands to be perfect doctors, and stressful working conditions. The negative impacts of burnout on medical students include impaired physical and mental health, decreased academic performance and lower chances of getting a job.